EDUCATION AS LIBERATION: JOURNEY FROM SILENCE TO SELFHOOD IN SHASHI DESHPANDE’ S THE BINDING VINE - Thakur, Smrity; Singh, Krishna Murari (International Journal of Research -GRANTHAALAYAH, 2025)
Shashi Deshpande’s novel The Binding Vine (1993) represents a new phase in her development as an artist, where silence is no longer an end but the beginning of a profound journey toward selfhood and social consciousness. In this novel, Deshpande crafts a powerful narrative that redefines education as a process of inner awakening, empathy, and liberation. The protagonist, Urmila, becomes a conduit for the suppressed voices of women silenced by societal norms, particularly through her discovery of Kalpana’s tragedy and Mira’s poetic anguish. Her journey from grief to awareness marks a movement from passive suffering to active engagement, where listening, reading, and reflecting functions as acts of learning and unlearning. Urmila does not rebel with loud defiance but with quiet resistance refusing to be complicit in the culture of silence. In doing so, she transforms into a support system for other marginalized women, allowing their stories to be heard and acknowledged. Education, in The Binding Vine, is thus portrayed as a liberating force that empowers women to reclaim their narratives and identities. It is through this inward and outward journey that Urmi and the reader discovers the strength to break the cycle of silence and walk toward a more self-aware, compassionate existence.